Psychosocial Challenges and HIV Prevention Barriers among High-Risk Youth in Deli Serdang, Indonesia - Nurhamida Fithri; Pratiwi Lumbantobing; Nona Try Agista; Wanri Lumbanraja (Journal of Public Health Indonesian, 2026)
Human Immunodeficiency Virus (HIV) remains a significant public health problem among high-risk youth in Indonesia. Psychosocial problems, stigma, discrimination, emotional isolation, and limited access to healthcare services continue to hinder HIV prevention efforts among vulnerable populations. This study aimed to explore psychosocial challenges and barriers to HIV prevention among high-risk youth in Deli Serdang, Indonesia. A qualitative study was conducted using in-depth interviews and focus group discussions involving people living with HIV/AIDS, key populations, healthcare workers, community leaders, and related stakeholders. Participants were selected using purposive sampling. Data were analyzed using thematic analysis to identify major psychosocial and social barriers associated with HIV prevention. The findings revealed several important challenges, including stigma and discrimination, fear of HIV status disclosure, limited family and social support, risky sexual behaviors, low self-confidence, psychological distress, and barriers to healthcare access. Social stigma and insufficient community education were also found to contribute to delayed HIV testing and treatment seeking. The study concludes that psychosocial burden and social barriers remain major obstacles to HIV prevention among high-risk youth in Deli Serdang. Strengthening psychosocial support, community education, stigma reduction programs, and accessible HIV services are essential to improve HIV prevention efforts among vulnerable populations.